Environmental microbiology : methods and protocols - Holmes, Andrew J.; Paulsen, Ian T. (Methods in molecular biology 1096, 2014)
An up-to-date view of molecular mechanisms for investigating microbial communities and their biological activities, this new volume of Environmental Microbiology: Methods and Protocols looks at recent advances that are having a big impact on the field such as metagenomics and other 'omics' technologies, NanoSIMS, as well as stable isotope probing and more. Conveniently divided into four parts, the first section looks at methods involved in sampling environmental microorganisms, the second profiles different methods for investigating the diversity and composition of microbial communities, the third focuses on techniques for analyzing biological activities in situ, and the final section examines high throughput 'omics' approaches for the characterization of environmental microbial communities. This book was written as part of the highly successful Methods in Molecular Biology series, and, as such, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Fully updated and authoritative, Environmental Microbiology: Methods and Protocols, Second Edition aims to provide an unprecedented glimpse into the structure, composition, and activity of microbial communities across diverse environments and illuminate their impact on global ecological processes.-- Source other than Library of Congress